Effect of psychosocial trauma and stress on sexual dysfunction in women with endometriosis - Fiala, Ludek; Lenz, Jiri; Bob, Petr (Medicine, 2021)
BACKGROUND: Endometrial tissue plays an important role in the regulation of female fertility and there is evidence that endometrial pathology (including endometriosis) is closely related to endocrine disorders. On the other hand, various neuroendocrine changes can be significantly affected by psychosocial stress. In connection with these findings, we tested the relationship between neuroendocrine changes, sexual dysfunction, psychosocial/traumatic stress, and dissociative symptoms in women with endometriosis. METHODS: A total of 65 patients with endometriosis were included in the study. Clinical examinations were focused on the biochemical analysis of neuroendocrine markers of endometriosis (cancer antigen 125 [CA 125] and cancer antigen 19-9 [CA 19-9]), estradiol, psychometric evaluation of sexual dysfunction, psychosocial/traumatic stress, and dissociative symptoms. RESULTS: The results showed significant Spearman correlations between the values of the revised range of sexual difficulties for sexual dysfunction (Revised Female Sexual Distress Scale), psychosocial/traumatic stress (Trauma Symptoms Checklist) (R = 0.31), and dissociative symptoms (Somatoform Dissociation Questionnaire) (R = 0.33). Positive correlations were also found between CA 125 and CA 19-9 (R = 0.63), and between CA 125 and the results of the values of the revised scale of sexual difficulties for sexual dysfunction (Revised Female Sexual Distress Scale) (R = 0.29). Also psychosocial/traumatic stress (Trauma Symptoms Checklist) significantly correlated with CA 125 (R = 0.38) and with CA 19-9 (R = 0.33). CONCLUSION: These results represent the first findings regarding the relationship of the neuroendocrine markers CA 125 and CA 19-9 and sexual dysfunction with trauma/stress-related symptoms and dissociative symptoms in women with endometriosis.
Keywords: somatoformní poruchy; antigen CA-19-9; Sexual Dysfunction, Physiological; Humans; Correlation of Data; neurosekreční systémy; Psychological Trauma; antigen CA-125; Female; dospělí; Psychology; korelace dat; sexuální dysfunkce fyziologická; lidé; CA-19-9 Antigen; psychické trauma; Dissociative Disorders; Adult; Psychological Techniques; ženské pohlaví; Somatoform Disorders; endometrióza; psychologické techniky; CA-125 Antigen; Endometriosis; disociační poruchy; Neurosecretory Systems; psychologie